2018
DOI: 10.1111/1749-4877.12317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rodent abundance and richness on cache pilfering

Abstract: Scatterhoarding is a common behavioral strategy to conserve food during periods of scarcity, but this type of food storage is vulnerable to theft or pilferage. A variety of environmental factors and cache characteristics influence the rate of pilferage. Here we investigate 2 environmental factors, which heretofore have not received much attention: the abundance and species richness of scatterhoarding animals in the vicinity of scatterhoarded seeds. We measured the rate of cache pilferage at 7 sites that differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Our results are also contrary to the conventional model that caches are pilfered at higher rates at lower seed abundance (Gálvez et al, ; Stapanian & Smith, , ). Recent study showed cache pilfering was highly dependent on rodent abundance (Dittel & Vander Wall, ), indicating that rodent abundance may be a larger factor than seed availability in affecting cache pilfering as scatter‐hoarder behavior is often driven by the seed:scatter‐hoarder ratio (Theimer, ; Zwolak & Crone, ). This may explain why cache pilfering rates are similar between the two seed rain periods of Q. mongolica , in which there was no difference in rodent abundances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are also contrary to the conventional model that caches are pilfered at higher rates at lower seed abundance (Gálvez et al, ; Stapanian & Smith, , ). Recent study showed cache pilfering was highly dependent on rodent abundance (Dittel & Vander Wall, ), indicating that rodent abundance may be a larger factor than seed availability in affecting cache pilfering as scatter‐hoarder behavior is often driven by the seed:scatter‐hoarder ratio (Theimer, ; Zwolak & Crone, ). This may explain why cache pilfering rates are similar between the two seed rain periods of Q. mongolica , in which there was no difference in rodent abundances.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have shown the tendency for rodents to cache fewer seeds when seed availability is high (Celis-Diez & Bustamante, 2005;Celis-Diez, Bustamante, & Vasquez, 2004;Sundaram, Lichti, Steele, Dalgleish, & Swihart, 2017). Although animals may store more seeds than they can consume when seed availability is high (Dittel & Vander Wall, 2018), rodents may have more opportunities to acquire food rather than recover their own caches at high level of seed abundance (Moore, McEuen, Swihart, Contreras, & Steele, 2007). Therefore, it is plausible that rodents spend more time foraging rather than caching, or even stop caching entirely in the face of a surfeit of food (Theimer, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among seed predators, however, rigorous intraspecific and interspecific competition for limited food resources is also widely witnessed (Christensen & Whitham 1993;Thayer & Vander Wall 2005). Therefore, the availability of seeds and the abundance of seed predators/dispersers can affect the quality and quantity of seed dispersal by altering per capita seed abundance (García et al 2007;García & Martinez 2012;Xiao et al 2013;Dittel & Vander Wall 2018).…”
Section: Introductionmentioning
confidence: 99%